Adiwiyata Madrasah Program: Strategies for Improving the Quality of Environmentally Conscious Madrasahs - Puspo Nugroho; Sanusi Sanusi; Jazaul Ichsan (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
The purpose of this research is to identify the standards for improving the quality of Adiwiyata madrasas, how the Adiwiyata madrasa quality improvement program works, and the obstacles that arise in enhancing the quality of Adiwiyata madrasas. This research uses the type of field research where the researcher directly engages in data collection and acts as the key instrument. The steps for data collection used include defining the scope of the study, the process of gathering information through observation, both structured and unstructured interviews, documentation of visual materials, and efforts to design protocols for recording or noting information. The data analysis stage is carried out through the stages of data reduction, data display, and conclusion verification. The results of this study found that the head of the madrasah established the Adiwiyata madrasah quality standards through the integration of Adiwiyata components into the eight national education standards, which include environmentally conscious policies, the implementation of an environment-based curriculum, participatory environment-based activities, and the management of environmentally friendly facilities and infrastructure. Second; The program to improve the quality of environmentally-oriented madrasahs is pursued through planning, action implementation, and periodic evaluation and monitoring of the adiwiyata program, supported by a democratic leadership model and emphasizing an environmental awareness spirit. Third; several obstacles that emerged include issues at the implementation level such as the relocation of trash bins, the adiwiyata program conflicting with the pesantren's ro’an program, the accumulation of plastic snack wrappers, and the lack of student awareness regarding the adiwiyata program, which still requires continuous strengthening and support.Keywords: Madrasah; Adiwiyata; Environmental Awareness; Program